Study on the prevalence of Zolpidem consumption in young people aged 15 to 24 in Cascavel – PR (Research, Society and Development, 2024)
Zolpidem is a hypnotic drug prescribed for the treatment of insomnia, with a rapid onset of action, promoting sleep in approximately 15 to 30 minutes after administration. Although effective, Zolpidem is not free from adverse effects. However, the abusive use of Zolpidem represents a significant concern since prolonged use or in doses higher than those prescribed can cause dependence. In this context, this study aimed to evaluate the prevalence of Zolpidem consumption among young people aged 15 to 24 years in Cascavel, PR. The methodological design followed a retrospective cross-sectional study, in which data from sales records of the drug Zolpidem were evaluated for young people aged 15 to 24 years, of both sexes, by a private commercial pharmacy located in Cascavel-PR. Thus, it was possible to infer the profile of Zolpidem consumption in this age group and region, with Zolpidem consumption being more prevalent among middle-aged adults, with a significantly lower demand among young people and elderly people over 80 years of age. In addition, there was a variation between 5 mg, 6.25 mg, 10 mg, and 12.5 mg, with a predominant concentration of Zolpidem among individuals, with the 10 mg dose being widely used more than the others. The results show the importance of establishing control and awareness-raising actions by health authorities, as providing valuable information to guide public health policies and educational interventions to prevent the misuse of Zolpidem.